2000
DOI: 10.1162/108819800569816
|View full text |Cite
|
Sign up to set email alerts
|

Life‐Cycle Assessment and Temporal Distributions of Emissions: Developing a Fleet‐Based Analysis

Abstract: Although the product-centered focus of life-cycle assessment has been one of its strengths, this analytical perspective embeds assumptions that may conflict with the realities of environmental problems. This ar ticle demonstrates, through a series of mathematical derivations, that all the products in use, rather than a single product, frequently should be the appropriate unit of analysis. Such a "fleet-centered" approach supplies a richer perspective on the comparative emissions burdens generated by alternativ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
66
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 82 publications
(72 citation statements)
references
References 14 publications
2
66
0
Order By: Relevance
“…Using this new impact assessment method, one case study has shown that conclusions from an LCA study might significantly vary when different time horizons are considered. Other publications (Dubreuil et al 2007;Field et al 2000;Hellweg 2001;Kendall and Price 2012;Kendall 2012) have presented similar conclusions even though some authors (Schwietzke et al 2011) minimize its relevance for biofuel scenarios.…”
Section: Introductionmentioning
confidence: 54%
See 2 more Smart Citations
“…Using this new impact assessment method, one case study has shown that conclusions from an LCA study might significantly vary when different time horizons are considered. Other publications (Dubreuil et al 2007;Field et al 2000;Hellweg 2001;Kendall and Price 2012;Kendall 2012) have presented similar conclusions even though some authors (Schwietzke et al 2011) minimize its relevance for biofuel scenarios.…”
Section: Introductionmentioning
confidence: 54%
“…In the last 15 years, however, compelling arguments have been proposed to explain why industrial and environmental dynamics might have significant impacts on the results of some LCA studies (Field et al 2000;Finnveden et al 2009;Graedel 1998;Owens 1997;Reap et al 2008;Udo de Haes et al 2002). Indeed, not considering temporal variability is now recognized as one of the shortcomings of the LCA methodology (ISO 14 040 and 14 044).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Systemic maps identify variables which may not typically be identified and considered in LCA studies but may have significant influence upon environmental impacts through cause-effect chains [11]. Suggestions for optimization are traditionally made on the basis of a single unit, not taking into account, for instance, the product line [12][13][14], infrastructure systems [15], the interrelations between the products and the infrastructure system. The traditional approach may hinder the possibilities of achieving higher levels of efficiency and of reduction of negative environmental impacts [16].…”
Section: The Case For a Systemic Perspective In Food Production Impromentioning
confidence: 99%
“…In addition, they lack a future time perspective regarding advances in material processing, technology development and changes in electricity production (Nordelöf et al 2014). However, when the goal is to assess new or changing technologies, transient effects may be important and cannot be captured with such static, single-product analysis (Field et al 2000). Moreover, if the goal is to explore solutions able to reduce overall environmental impacts (e.g., to meet medium/long-term policy targets), both scale and timing of adoption may influence the results (Hillman and Sandén 2008;Stasinopoulos et al 2011).…”
Section: Introductionmentioning
confidence: 99%